Dinosaurus : the complete guide to dinosaurs - Parker, Steve 1952- (Buffalo, New York : Firefly Books (U.S.), Inc., 2016)
Brimming with research from digs in North America, Mongolia, Europe, China and elsewhere, Dinosaurus is an encyclopedic and vividly illustrated reference for all ages.
Conquerors of the land -- The first dinosaurs -- The small meat-eaters -- The great predators -- Ostrrich dinosaurs -- The giants -- Bird-foot dinosaurs -- The duckbills -- The boneheads -- Armored dinosaurs -- Plated dinosaurs -- Horned dinosaurs -- Other creatures of the dinosaur age -- After the dinosaurs.
Second edition by Firefly Books.
Copyrighted by Quintet Publishing.
"A Firefly book"--Back cover.
Includes index.
104547
Keywords: Dinosaurs; Dinosaurs -- Encyclopedias; Dinosaurs -- Pictorial works; Paleontology; Dinosaures